Influence of Disorders of Fatty Acid Metabolism, Arterial Wall Hypoxia, and Intraplaque Hemorrhages on Lipid Accumulation in Atherosclerotic Vessels - A. N. Osipenko (Acta Biomedica Scientifica)
The review describes a number of competing views on the main causes of cholesterol accumulation in atherosclerotic vessels. On the one hand, unregulated cholesterol influx into arterial intima is primarily related to the increasing proportion of atherogenic lipoproteins in the lipoprotein spectrum of blood. On the other hand, the leading role in this process is assigned to the increased permeability of endothelium for atherogenic lipoproteins. The increased ability of arterial intima connective tissue to bind atherogenic blood lipoproteins is also considered to be the leading cause of cholesterol accumulation in the vascular wall. The key role in cholesterol accumulation is also assigned to unregulated (by a negative feedback mechanism) absorption of atherogenic lipoproteins by foam cells. It is suggested that the main cause of abundant cholesterol accumulation in atherosclerotic vessels is significant inflow of this lipid into the vascular wall during vasa vasorum hemorrhages.The article also provides arguments, according to which disorder of fatty acid metabolism in arterial wall cells can initiate accumulation of neutral lipids in them, contribute to the inflammation and negatively affect the mechanical conditions around the vasa vasorum in the arterial walls. As a result, the impact of pulse waves on the luminal surface of the arteries will lead to frequent hemorrhages of these microvessels. At the same time, adaptive-muscular intima hyperplasia, which develops in arterial channel areas subjected to high hemodynamic loads, causes local hypoxia in a vascular wall. As a result, arterial wall cells undergo even more severe lipid transformation. Hypoxia also stimulates vascularization of the arterial wall, which contributes to hemorrhages in it. With hemorrhages, free erythrocyte cholesterol penetrates into the forming atherosclerotic plaque, a part of this cholesterol forms cholesterol esters inside the arterial cells. The saturation of erythrocyte membranes with this lipid in conditions of hypercholesterolemia and atherogenic dyslipoproteinemia contributes to the process of cholesterol accumulation in arteries.